Faktor Yang Mempengaruhi Kinerja Pemasaran Di Waralaba ThaiTea Fremlit - Prabowo, Dania Monica Permana Putri Hadi (Jurnal Manajemen DIVERSIFIKASI, 2022)
Increasingly increasing franchise competition to compete for the existing market causes each industry to establish the right strategy in marketing its products. This study aims to determine product innovation and competitive advantage affect marketing performance. This research uses quantitative research. The population in this study is Thai Tea Fremilt consumers as many as more than 1000 people. The sample in this study was 100 respondents. The instrument used was a questionnaire as many as 21 questionnaire items. The analysis technique used is regression analysis, T test, F test and determination coefficient. The results in this study that product innovation has an effect on marketing performance, competitive advantage also affects marketing performance, then jointly product innovation and competitive advantage affect marketing performance. In addition, 88.2% of the effect of product innovation and competitive advantage on marketing performance. This is because the innovation of a product at Thai Tea Fremilt makes consumers curious, so they try new things at Thai Tea Fremilt that have never been tried before.